2014
DOI: 10.3745/jips.02.0002
|View full text |Cite
|
Sign up to set email alerts
|

Skin Segmentation Using YUV and RGB Color Spaces

Abstract: Abstract-Skin detection is used in many applications, such as face recognition, hand tracking, and human-computer interaction. There are many skin color detection algorithms that are used to extract human skin color regions that are based on the thresholding technique since it is simple and fast for computation. The efficiency of each color space depends on its robustness to the change in lighting and the ability to distinguish skin color pixels in images that have a complex background. For more accurate skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 13 publications
0
38
0
1
Order By: Relevance
“…[6][7][8][9][10][11][12][13] were successfully applied to skin detection problem. Some studies concluded that the skin detection performance can be improved when using two different color spaces together [14][15][16]. According to the above studies, this paper also applies a combined color space, RGBUV, which was proven to be effective by [14], to skin detection problem.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…[6][7][8][9][10][11][12][13] were successfully applied to skin detection problem. Some studies concluded that the skin detection performance can be improved when using two different color spaces together [14][15][16]. According to the above studies, this paper also applies a combined color space, RGBUV, which was proven to be effective by [14], to skin detection problem.…”
Section: Introductionmentioning
confidence: 92%
“…Some studies concluded that the skin detection performance can be improved when using two different color spaces together [14][15][16]. According to the above studies, this paper also applies a combined color space, RGBUV, which was proven to be effective by [14], to skin detection problem. For (ii), to classify whether a pixel is skin or not, the majority of previous studies usually focused on two groups of methods: the thresholding and the machine learning methods.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A combination of YUV and RGB is used in [3] for skin detection. Other related works using color space combination are also reported in [3].…”
Section: Introductionmentioning
confidence: 99%